2020
DOI: 10.1186/s13071-020-04149-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of community-wide, mass drug administration on aggregation of soil-transmitted helminth infection in human host populations

Abstract: Background: Soil-transmitted helminths (STH) are intestinal parasites estimated to infect over 1.5 billion people. Current treatment programmes are aimed at morbidity control through school-based deworming programmes (targeting school-aged children, SAC) and treating women of reproductive age (WRA), as these two groups are believed to record the highest morbidity. More recently, however, the potential for interrupting transmission by treating entire communities has been receiving greater emphasis and the feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Modelling studies have suggested that soil-transmitted helminth infections in endemic communities become increasingly clustered as disease prevalence drops, determined in part by patterns of individual participation during MDA, with important consequences for the probability of achieving transmission interruption. 32 , 33 Developing a stronger empirical understanding of the effects of systematic non-treatment on transmission of soil-transmitted helminths and other neglected tropical diseases, and the identification of new approaches to ensure treatment of identified subgroups, remain urgent priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling studies have suggested that soil-transmitted helminth infections in endemic communities become increasingly clustered as disease prevalence drops, determined in part by patterns of individual participation during MDA, with important consequences for the probability of achieving transmission interruption. 32 , 33 Developing a stronger empirical understanding of the effects of systematic non-treatment on transmission of soil-transmitted helminths and other neglected tropical diseases, and the identification of new approaches to ensure treatment of identified subgroups, remain urgent priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of S. haematobium in Kwale (similar study site to the current study) among adults was 18.2% in 2010 [ 11 ] and 15.07% in 2018 among people of all age groups and gender [ 12 ]. Three major STH infections are caused by roundworms ( Ascaris lumbricoides ), whipworms ( Trichuris trichiura ), and the hookworms ( Ancylostoma duodenale and/or Necator americanus ) [ 13 15 ]. Generally a combination of factors have been implicated in STH infections which include poverty, lack of sanitation, and inadequate hygiene [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…What has not been appreciated, however, is that repeated rounds of MDA, the favoured control option for human helminth infections, tend to drive parasite aggregation to higher and higher levels (very small k values) [9]. Very recent studies point to persistent non-adherence to treatment being the causative mechanism [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, diagnostics measure the intensity of infection using eggs counts from urine, stool or blood samples or DNA detection (qPCR) methods. However, information is beginning to emerge from large scale trials of how best to conduct deworming programmes, such as TUMIKIA and DeWorm3, that suggest under repeated rounds of treatment the degree of worm aggregation in the targeted communities rises steeply [7][8][9]. The generative mechanism or mechanisms are poorly understood at present, but non-compliance to treatment in a small proportion of the population looks to be one of great importance [10,11].…”
Section: Introductionmentioning
confidence: 99%